Kajian Penerapan Metode Intrusion Prevention System Di Jaringan Internet Dan Intranet Universitas Riau - H, Irfan Kurniadi; Ali, Irsan Taufik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The development of Information Technology makes an information security is very important, especially on a network connected to the internet. The imbalance between every development of a technology is not accompanied by developments in the security system itself, thus quite a lot of systems are still weak. This weakness is able to create a threat, either from within or from outside. The security system used by the University of Riau today is the Firewall-DMZ security system that is a security system that controls, supervises, filters and identifies incoming traffic and protects servers that are accessible to the public. Intrusion Prevention System as a security system that can prevent a threat to the information network. Intrusion Prevention System (IPS) combines firewall techniques and Intrusion Detection System (IDS) methods very well. This technology can prevent attacks that will enter the local network by checking and recording all data packets and recognizing the sensor data packets, when an attack has been identified, Intrusion Prevention System (IPS) will deny access and record all identified data packets. The result of this research is to apply snort security system based on snort network of Riau University by simulating some attack experiments that are resolved well by IPS, so it can be a consideration for University Computer Center of Riau to implement security system which is automated in intranet and internet university Riau.Keywords : Intrusion Prevention System, IPS, IDS, Snort, Network Security, Network.